Pemberdayaan siswa IX SMA Al-Azhar 15 Semarang melalui pelatihan pembuatan eco enzyme handsoap - Nofitasari, Titin Ayuk; Ningrum , Hilda Putri; Sutono, Adinda Aprilya Sulvessy; Armanda, Dian Triastari; Kusumarini, Niken (Universitas Mataram, 2025)
The accumulation of organic waste causes new problems such as environmental pollution, methane gas production that causes global warming, and sources of diseases that can affect human health. One solution in managing organic waste is the manufacture of ecoenzymes. Ecoenzymes have many benefits in everyday life such as household cleaning fluids, vegetable and fruit cleaners, insect repellents and plant fertilizers. The Biology study program of UIN Walisongo Semarang through community service activities tries to process waste into a useful and valuable product with the participants of this service being class IX students of SMA Al-Azhar 15 Semarang. The method used in this training begins with coordination with teachers, a pre-test before the training, introduction to the material, training in making eco enzyme hand soap, and a post-test. Based on the results of the pre-test, students stated that eco enzyme can be used as fertilizer, toilet cleaner, dish soap, natural pesticide, can neutralize river water and fertilize plants. From the survey results of the level of student interest in becoming entrepreneurs before the training was conducted, it was found that 13 students were interested in becoming entrepreneurs, 11 students were very interested, 11 students were not interested, and 2 students were very uninterested in becoming entrepreneurs. After the eco enzyme handsoap making training was conducted, the level of student interest in becoming entrepreneurs increased with the results of 16 students interested in becoming entrepreneurs, 10 students were very interested, 8 students were not interested, 2 students were very uninterested, and there were 2 students who did not answer.